Robust and stable ruthenium alloy electrocatalysts for hydrogen evolution by seawater splitting. (1st August 2016) - Niu, Xiaoman; Tang, Qunwei; He, Benlin; Yang, Peizhi
Graphical abstract: Highlights: Ruthenium alloy catalysts are used for hydrogen evolution from seawater. The resultant ruthenium alloy electrocatalysts are robust and stable for HER The Ti foil supported RuCoMox are promising for seawater splitting. Abstract: Seawater splitting by complicated electrocatalytic processes is promising for hydrogen evolution. Here we present a series of robust electrodes by electrodepositing RuCo and RuCoMox alloys on Ti foil substrates for hydrogen evolution from seawater splitting. The preliminary results demonstrate that Ti foil supported RuCo and RuCoMox alloy electrodes require overpotentials of ∼387 and ∼550 mV to drive the hydrogen evolution reaction (HER) at a benchmark current density of 10 mA cm −2, respectively. Moreover, the resultant Ti foil supported RuCoMox electrode shows excellent stability under persistent operation at a constant current density of −1.2 V over 12 h.